The Influence of Online Customer Reviews on Hotel Room Purchase Decisions Through Online Travel Agents at Hotel Truntum Padang - Agda, Agda Treusna Pamungkas; Hijriyantomi Suyuthie (Journal of Multidimensional Management, 2025)
The rapid development of information technology has significantly transformed the hospitality industry, where online customer reviews (OCRs) have become a crucial determinant of consumer behavior in hotel booking decisions through Online Travel Agents (OTAs). This study aims to examine the effect of OCRs on hotel room purchase decisions at Hotel Truntum Padang. Employing a quantitative causal approach, data were collected from 100 respondents using purposive sampling and analyzed through simple linear regression with SPSS version 26. The results revealed that OCRs have a positive and significant impact on purchase decisions, explaining 35.9% of the variance, while the remaining 64.1% is influenced by other factors. These findings confirm the essential role of OCRs in shaping customer trust, credibility, and intention to book, where positive reviews encourage bookings and recommendations, while negative reviews may reduce consumer trust. From a managerial perspective, the study emphasizes the importance of actively managing OCRs by encouraging feedback, responding to negative comments, and utilizing customer reviews as a strategic tool to enhance competitiveness in the hospitality market.